Answer:
A
Explanation:
Before we can add the 2 fractions we require them to have a common denominator.
Multiply the numerator/ denominator of the first fraction by x
Multiply the numerator/ denominator of the second fraction by (x + 3)
=
+
![((x-2)(x+3))/(x(x+3))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q6komrl9nqvcl2fbtlo8pfyoj4l41keun7.png)
Now simplify the numerator, leaving the denominator
=
![(3x^2+x^2+x-6)/(x(x+3))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wzpt0y3bcb6f4zbc3w2b1ceyrni1mq09g3.png)
=
→ A